2020
DOI: 10.1007/s11240-020-01949-5
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and HPLC-DAD, UPLC MS/MS analysis of oenothein B and phenolic acids in shoot cultures and in regenerated plants of fireweed (Chamerion angustifolium (L.) Holub)

Abstract: In this study, a micropropagation protocol using nodal explants from in vitro grown plants of Chamerion angustifolium (L.) Holub was developed and analysis of oenothein B and selected phenolic acids in shoot cultures was performed for the first time. For shoot induction and multiplication Murashige and Skoog’s (MS) basal medium supplemented with 2-isopentenyladenine (2iP), zeatin (Z) and 6-benzyloaminopurine (BAP) was used. 2iP was the most responsive in terms of promoting shoots per explant with the maximum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The micropropagation efficiency depends on culture conditions, selection of plant growth regulators (PGRs), micropropagation technique, type of explant, age of donors' plants and genotype. Organogenesis from root explants (Turker et al 2008;Dreger et al 2016) and nodal explants of fireweed (Dreger et al 2020) was reported previously. A higher regeneration rate (> 30 shoots per explants) was noted for root explants (Turker et al 2008;Dreger et al 2016), but without respect to the genotype effect.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The micropropagation efficiency depends on culture conditions, selection of plant growth regulators (PGRs), micropropagation technique, type of explant, age of donors' plants and genotype. Organogenesis from root explants (Turker et al 2008;Dreger et al 2016) and nodal explants of fireweed (Dreger et al 2020) was reported previously. A higher regeneration rate (> 30 shoots per explants) was noted for root explants (Turker et al 2008;Dreger et al 2016), but without respect to the genotype effect.…”
Section: Discussionmentioning
confidence: 83%
“…Comparable oenothein B content (24.6 mg g −1 DW) in Ch. angustifolium shoot cultures was determined previously (Dreger et al 2020). Presence of caffeic acid pentoside is reported for the first time in in vitro cultures of fireweed, although this compound and other caffeic acid derivatives are commonly found in medicinal plants with strong antioxidant action (Tajner-Czopek et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main components of EA are polyphenols, especially hydrolyzable tannins (ellagitannins), flavonoids, and phenolic acids [ 6 , 17 , 18 , 19 ]. The main phenolic acids are, among others, the following: gallic acid, 4-hydroxybenzoic acid, caffeic acid, chlorogenic acid, rosmarinic acid, ellagic acid, protocatechinic acid, and cinnamic acid [ 8 , 12 , 20 , 21 ], while the major flavonoids are the following: quercetin, myricetin, myricitrin, isomyricitrin, kaempferol, rutin, epicatechin hyperoside and isoquercetin [ 11 , 21 ]. Another important group is tannins, among others, oenothein B (OeB), which is mentioned as one of the main substances with the biological activity of this plant [ 6 , 20 , 22 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The main phenolic acids are, among others, the following: gallic acid, 4-hydroxybenzoic acid, caffeic acid, chlorogenic acid, rosmarinic acid, ellagic acid, protocatechinic acid, and cinnamic acid [ 8 , 12 , 20 , 21 ], while the major flavonoids are the following: quercetin, myricetin, myricitrin, isomyricitrin, kaempferol, rutin, epicatechin hyperoside and isoquercetin [ 11 , 21 ]. Another important group is tannins, among others, oenothein B (OeB), which is mentioned as one of the main substances with the biological activity of this plant [ 6 , 20 , 22 ]. EA also contains a small amount of the essential oil in leaves and stems, composed mainly of terpenes such as anethole, β-bisabolene, α-caryophyllene, and caryophyllene, eugenol, linalool, pelargol, and menthol [ 6 , 23 , 24 ].…”
Section: Chemical Compositionmentioning
confidence: 99%